2003
DOI: 10.1093/gerona/58.12.b1074
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decline of In Vitro Migration (Basal and Stimulated by IGF-1 or Insulin) of Human Vascular Smooth Muscle Cells

Abstract: Since biological aging causes a decrease in functions such as cell proliferation, we have studied the possible effect of age on the migration capacity of human vascular smooth muscle cells (SMCs). To this aim, the migration activity of cultured SMCs from arteries of male human donors ranging in age from 43-77 years was determined in a Boyden chamber, under basal conditions and after insulin-like growth factor-1 (IGF-1) or insulin stimulation. Migration activity decreased with donor age (r2 = 87%, 85%, and 78%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Interestingly, evidence has indicated that suppression of these growth factors or their receptors prolongs lifespan and delays in age-associated functional decline. Our observations in which IGF-1 induces an increase in migration and proliferation of VSMCs are in line with many of the previous results [17,18] although it contradicts some of the results obtained from human SMCs [15,16]. It has been demonstrated that late passage VSMCs possess a higher proliferative capacity in response to fetal bovine serum associated with enhanced matrix metalloprotein-9 expression in comparison with young cells [20].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Interestingly, evidence has indicated that suppression of these growth factors or their receptors prolongs lifespan and delays in age-associated functional decline. Our observations in which IGF-1 induces an increase in migration and proliferation of VSMCs are in line with many of the previous results [17,18] although it contradicts some of the results obtained from human SMCs [15,16]. It has been demonstrated that late passage VSMCs possess a higher proliferative capacity in response to fetal bovine serum associated with enhanced matrix metalloprotein-9 expression in comparison with young cells [20].…”
Section: Discussionsupporting
confidence: 76%
“…Rat VSMC may not be the best model reminiscent of human VSMC life cycle [15,16], which might be a major limitation of our experiments. In contrast to human VSMCs which undergo senescence after repeated cell divisions, VSMCs from rats escape senescence following repeated subculture and may be converted to permanently de-differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another known change associated with cellular senescence is the reduced ability to migrate (Schneider and Mitsui 1976;Sandeman et al 2000;Reed et al 2000;Ruiz-Torres et al 2003). This impaired ability to migrate may be related to changes which occur to the cytoskeleton during cellular senescence (Nishio and Inoue 2005).…”
Section: Biological Impact Of the Senescent Phenotypementioning
confidence: 99%